CALCULATION OF POLLUTION DYNAMICS NEAR RAILWAY TERRITORY DURING COAL TRANSPORTATION - Biliaiev, M. M.; Oladipo, M. O. (Science and Transport Progress, 2017)
Purpose. The article is aimed to develop 3D numerical model for the prediction of atmospheric pollution during transportation of bulk cargo in the railway car. Methodology.To solve this problem, it was developed three-dimensional numerical model, based on the use of the transport equation of dust pollution in the air by the wind and atmospheric turbulent diffusion. For the numerical integration of the simulating equation of the dust transport the implicit difference scheme was used. When constructing a difference scheme, it was carried out prior splitting of the original transport equation into the sequence of solutions of three equations. The first of them takes into account the transport of dust in paths, the second equation – dust transport under the influence of atmospheric turbulent diffusion, and the third equation –change of the dust concentration in the air due to its emissions from the cars.Unknown value of the pollutant concentration at every step of splitting is determined by the explicit scheme – the method of running account, which provides a simple numerical implementation of splitting equations. The developed numerical model is the basis for specialized computer program. On the basis of the constructed numerical model we carried out a computational experiment to assess the level of air pollution at the railway station during the motion of train with coal. Findings. Authors developed 3D numerical model, which belongs to the class of «screening models». This model takes into account the main physical factors affecting the process of dispersion of dust pollution in the atmosphere during coal transportation. The proposed numerical model requires low cost of computer time in the practical implementation on small and medium-power computers. This model can be used for rapid calculations of the dynamics of air pollution when transporting coal by rail. Calculations to determine the pollutant concentration and formation of the contamination zone at Enugu station were performed. The results of physical experiment, allow us to recommend the use of additional specially shaped boards to minimize the removal of coal dust from gondola cars. Originality.It was created3D numerical model that makes it possible to take into account significant physical factors that influence the process of dust dispersion in the atmosphere. The model allows calculating the formation of pollution zones during transportation of coal by rail. Practical value. The effective numerical model of the class «screening models» for rapid calculation of the level of air pollution from coal transport by rail was considered. The model can be applied in the development of environmental protection measures in the operation of rail transport. The proposed model allows you to quickly calculate the 3D transfer of dust in the air.